2022
DOI: 10.3390/ijerph19084857
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German Version of the Moral Injury Symptom and Support Scale for Health Professionals (G-MISS-HP) and Its Correlation to the Second Victim Phenomenon

Abstract: Introduction: Comparable to second victim phenomenon (SVP), moral injury (MI) affects health professionals (HP) working in stressful environments. Information on how MI and SVP intercorrelate and their part in a psychological trauma complex is limited. We tested and validated a German version of the Moral Injury Symptom and Support Scale for Health Professionals (G-MISS-HP) instrument, screening for MI and correlated it with the recently developed German version of the Second Victim Experience and Support Tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 44 publications
3
23
5
Order By: Relevance
“…The study results indicated that Iranian health care professionals obtained three acceptable factors for the MISS-HP that explained nearly 60% of the variance. The variance obtained in the present study was higher than that reported in the German (Trifunovic-Koenig et al, 2022), Chinese (Zhizhong et al, 2020), and the United States versions (Mantri et al, 2020). In the Chinese version of the MISS-HP, EFA suggested three factors that accounted for 59% of the variance (Zhizhong et al, 2020).…”
Section: Construct Validity: Structural Validitycontrasting
confidence: 66%
See 3 more Smart Citations
“…The study results indicated that Iranian health care professionals obtained three acceptable factors for the MISS-HP that explained nearly 60% of the variance. The variance obtained in the present study was higher than that reported in the German (Trifunovic-Koenig et al, 2022), Chinese (Zhizhong et al, 2020), and the United States versions (Mantri et al, 2020). In the Chinese version of the MISS-HP, EFA suggested three factors that accounted for 59% of the variance (Zhizhong et al, 2020).…”
Section: Construct Validity: Structural Validitycontrasting
confidence: 66%
“…The study results showed acceptable psychometric properties of the Persian version of MISS-HP. A review of the literature showed that due to the COVID-19 outbreak and the possibility of moral injury of health care professionals, the Chinese (Zhizhong et al, 2020), German (Trifunovic-Koenig et al, 2022), Turkish (Üstün, 2022), and the United States (Mantri et al, 2020) versions of this questionnaire have been used and measured psychometrically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the employees are found to experience negative emotions such as frustration and anger, emotional exhaustion, cynical attitudes, and depersonalization toward patients, resulting in quitting or considering quitting their position [ 10 ]. Ethical dilemmas and moral distress should be distinguished from more acute and traumatizing care-related effects, such as second victim effects and moral injuries, which result from unforeseeable and acute incidents during treatment [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%